No end save victory : how FDR led the nation into war - Kaiser, David E. 1947- (Basic Books, a member of the Perseus Books Group, 2014)
Describes the challenges faced by Franklin Delano Roosevelt in the first 100 days of his presidency as well as highlights the preparations he put into place, including military expansions, that ultimately enabled the United States to be victorious in World War II.